SOME THE EQUATIONS WITH RESPECT TO THE NEW VARIABLES SYSTEM OF EQUATIONS TO SOLVE - Ahmedova Gavhar; Meliboyeva Yulduzxon (Galaxy International Interdisciplinary Research Journal, 2023)
This in the article some equations new equations with respect to variables system to solve to bring In some cases, the solution of complex algebraic equations is reduced to the solution of simple equations as a result of changing variables. Only students when solving an equation, they do not immediately notice how the given equation can become simpler when replacing the unknowns. In some cases, the equations are reduced to solving a system of equations with respect to the newly introduced variables . We give examples of solving such equations.